Optimization of the cold profiling process through SMED - Vieira, T. (2020)
In a more and more competitive and industrialized market, it is essential that companies realize that the way forward must go through the optimization of their production processes, reducing the costs and increasing product quality. Nowadays it’s necessary to adopt innovative management models that can provide increased productivity at minimal costs, such as the Lean thinking. The metalworking industry is integrated into one of the most competitive existing markets in Portugal. Given this, it’s fundamental to reduce the waste in all sectors of the production process, using the good Lean principles and practices, such as the Single Minute Exchange of Die, also known as SMED methodology. This paper presents a project of implementing the SMED methodology in the cold profiling process, in a population of five different profiling machines. The results of the SMED implementation show an average OEE improvement of 10,8%.